Physical activity of girls with Turner’s syndrome Ocena poziomu aktywności fizycznej dziewcząt z zespołem Turnera - Edyta Sienkiewicz-Dianzenza; Katarzyna Milde; Paweł Tomaszewski; Mirosława Frąc (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: Typical features in Turner’s syndrome such as growth deficit and abnormal body proportions may result in perceiving Turner girls as being physically weaker. Hence, physical activity systematically undertaken by those girls would be of utmost importance for keeping healthy and for an adequate relation of body fat to muscle mass, sustaining or increasing physical capacity and for prevention of osteoporosis and hypertension. Aim of the study: To assess the level of physical activity of girls with Turner’s syndrome. Materials and methods: 45 girls with Turner’s syndrome in the junior high school (n=21) or high school (n=24) age volunteered to participate in the study performed during a summer camp. Physical activity was assessed by applying short version of International Physical Activity Questionnaire (IPAQ). Results: No differences between younger and older girls were found with respect to practising intensive or moderate activities as well as to time spent on walking. About 47% of girls with Turner’s syndrome declared practising intensive and 62% of them moderate activities; only 9% declared no walking for at least 10 minutes without significant breaks. The level of physical activity expressed in MET units (minutes/week) was comparable in both groups of girls and was not correlated with the BMI of the girls studied. Conclusions: The results of the presented study suggest that the level of physical activity of girls with Turner’s syndrome is relatively high. However, these observations should be interpreted very cautiously especially when confronted with our earlier reports, in which Turner girls exhibited low level of physical fitness, low interest in practicing sports and unsatisfactory participation in physical education classes. It may thus be supposed that the declared level of physical activity of girls with Turner’s syndrome was overestimated. We conclude that a relatively high declared level of physical activity may be a result of improper interpretation or lack of understanding of the questions, specific period of performing the study or simply wish of Turner girls to be perceived better.